(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Middle adolescence is a life developmental stage where a child faces the process of puberty- related changes. Ages 14-17 are prone to psychological and physical adjustments, and transitioning from childhood to adolescence may be filled with many challenges and understanding. Adolescents start to be more explorative in social, emotional, and cognitive development aspects. In this time, parents can be a great factor and guidance to help the growing children not be missing in the process of being a teenager. The researchers aim to determine not only the challenges middle adolescents and parents encounter upon creating parent-child relationships and building potentials but also the factors affecting them, such as adolescent’s autonomy and reliance on their parents. This study was conducted to identify problems and shortcomings and is up to create an output to bring solutions for the challenges and persons involved. Results showed that helicopter and positive parenting both cultivate potential among middle adolescents, despite the contrast between the two. It is also revealed that the factors and conflicts presented positively relate to adolescents and parents; however, some of the data showed academic and child dependency and material needs demands as problems arising. The data was gathered from 50 pairs of respondents, with most of the adolescents being 17 with a percentage of 30. Middle adolescents are highly affected by the way parents choose to rear them. Although there are factors or conflicts arising in the parent-child relationship, they could be faced correctly if there is guidance from the parent and understanding from the middle adolescent. This study objects to further explore parenting styles, especially the newest type of parenting styles, and how this matters to the growth of adolescents and their potential. In addition, it is to also present solutions to the problems the researchers had revealed from the data gathered.